(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Shift work, prevalent in nursing, significantly impacts the health and well-being of nursing professionals. This study examines the multifaceted effects of shift work on nurses, focusing on physical health, mental health, and job performance. A comprehensive review of existing literature and a survey conducted among nursing professionals reveal key findings. The adverse health effects include sleep disorders, cardiovascular issues, and gastrointestinal disturbances. Mental health impacts encompass increased stress levels, burnout, and depression. Furthermore, the irregular work hours detrimentally affect job performance, leading to higher rates of errors and reduced patient care quality. The study underscores the necessity for organizational strategies and policies aimed at mitigating the negative consequences of shift work, thereby improving the overall well-being and efficiency of nursing professionals.